FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) PADA REMAJA DI SMA N 1 SANDEN - Fadzilla, Vichi; Djannah, Sitti Nur (Universitas Ahmad Dahlan, 2019)
Background: Teenagers have a very complex problem along with the transmission period they experienced. In general, adolescents expressed the need for reproductive health services that is equal to 94.55% of the total respondents. Only a few respondents stated that they had used a youth service center that was 23.42%. Utilization of Youth Information and Counseling Center is still very low in Indonesia. Strategies to improve the utilization of the Youth Information and Counseling Center are urgently needed. This study was conducted to determine the relationship between knowledge, attitudes and role of peer educators with the utilization of PIK-R in adolescents in SMA N 1 Sanden.Â Method: This research is a quantitative analytical research with cross sectional approach. Sampling using purposive sampling technique and obtained a sample of 75 members of PIK-R in SMA N 1 Sanden. Measurement of variables using questionnaires and tested using Chi square test. Results: The results of this study indicate that the role of peer educators has a significant relationship with the utilization of PIK-R (p = 0.008), no knowledge relation (p = 0.218) and attitudes about reproductive health (p = 0.072) with PIK-R utilization. Peer educator role variables have RP = 2.323 (95% CI = 1.284-4.202) more than the number 1 means peer educator role is really risk factor. Knowledge and attitude variable have RP value = 0.590 (95% CI = 0.278-1.252) and RP = 1.798 (95% CI = 1.029-3.143). Conclusion: There is a significant relationship between the role of peer educators and the utilization of PIK-R in adolescents in SMA N 1 Sanden.